Coordinating public and private sustainability green energy policy, international trade law, and economic mechanisms - Partain, Roy ca. 20./21. Jh (Routledge, 2020)
"This book demonstrates the need to coordinate private and corporate actors with national and global sustainable climate policies, with conventions in the spheres of green energy laws, as well as from the spheres of commercial, trade, and other private law. While many states have joined together in the Paris Agreements in support of green energy policies, it remains a stark reality that most of the efforts to reduce greenhouse emissions remain with private actors who operate the various industries, vehicles, and vessels that emit the gases in target. The risks of anthropogenic climate change cannot be solved by environmental law alone and will need complementary support from commercial, corporate, and private law. However, aspects of commercial law, securities law, and trade law can be shown to frustrate certain aspects of green energy policies, resulting in damaging "green paradoxes". It raises issues associated with corporate social responsibility and green paradoxes, with international trade laws, and with liability risks for misrepresenting the state of feasible green energy technologies. The book will be of interest to students and scholars in the fields of energy law, environmental law, and corporate law"--
Keywords: Internationales Umweltrecht; Nachhaltigkeit; Klimaänderung; Sustainable development / Law and legislation; Environmental law, International; Climatic changes / Law and legislation; Climatic changes / International cooperation; Foreign trade regulation; Greenhouse gases / Law and legislation; Clean energy